The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/da.22383
|View full text |Cite
|
Sign up to set email alerts
|

Depression Mediates the Relation of Insomnia Severity With Suicide Risk in Three Clinical Samples of U.S. Military Personnel

Abstract: Across three clinical samples of military personnel, depression explained the relationship between insomnia severity and suicide risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 43 publications
2
33
2
Order By: Relevance
“…Acute and chronic stressors (and in particular interpersonal difficulties) are predictive of suicidal behavior (Bryan, Clemans, Leeson, & Rudd, 2015;Foster, 2011;Zhang, Jia, Zhang, Wang, & Liu, 2015). Unfortunately, individuals exposed to ACE are more likely to experience subsequent negative life events.…”
Section: Interpersonal Functioningmentioning
confidence: 99%
“…Acute and chronic stressors (and in particular interpersonal difficulties) are predictive of suicidal behavior (Bryan, Clemans, Leeson, & Rudd, 2015;Foster, 2011;Zhang, Jia, Zhang, Wang, & Liu, 2015). Unfortunately, individuals exposed to ACE are more likely to experience subsequent negative life events.…”
Section: Interpersonal Functioningmentioning
confidence: 99%
“…For instance, one possible explanation of the sleep/suicide relationship is that sleep operates indirectly to increase suicide risk, because sleep problems increase the likelihood of depression (Baglioni et al, 2011) and depression, in turn, increases the risk of suicidal thoughts and behaviours (Harris & Barraclough, 1997). Findings from studies examining the interrelations between depression, sleep problems and suicidality are mixed, with divergent patterns of results emerging from studies examining insomnia (Bryan et al, 2015, Nadorff et al, 2014, Nadorff et al, 2013, Ribeiro et al, 2012). However, research examining nightmares has consistently shown an association between nightmares and suicidal thoughts and behaviours, independent of the effects of depression (Pigeon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant comorbidity between substance abuse involving stimulants and sleep disorders. Sleep is essential for psychological and physical wellbeing (Tufik et al, 2009) and disrupted sleep has been associated with reduced cognitive function (Qureshi et al, 2014), increased risk of depression (Zhai et al, 2015) and risk of suicide in depressed patients (Bryan et al, 2015), dysregulation of the hypothalamicpituitary-adrenal axis (Castro-Diehl et al, 2015), and increased risk of developing metabolic syndrome (Troxel et al, 2010), obesity (Buxton and Marcelli, 2010), and heart disease (Grandner et al, 2012;Appelhans et al, 2013).…”
Section: Introductionmentioning
confidence: 99%